Kontribusi Riil Pembangunan Infrastruktur Terhadap Peningkatan Ekonomi di Pedesaan - Zulfahmi, Muhammad; Fatihin, Muhamad Khairul; Dani, Rifaldi Rahman; Prabawa, Windhi Gita; Sopyan, Dodi (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the contribution of Rural bridge construction to the economic development of the community, specifically focusing on Dusun Cemara, Kabupaten Lombok Barat. This research uses a qualitative approach; data sources are obtained from primary data through interviews with village officials and local communities. Secondary data is also used to support the research, data sourced from government documents, and relevant literature. Dusun Cemara with great potential in the fisheries sector and marine tourism, is still constrained by the lack of adequate road and bridge infrastructure, so the government built a suspension bridge with the aim of improving accessibility and community mobility. The results showed that post-bridge construction, there was an increase in accessibility which ultimately affected the economy in several vital local sectors. This finding is in line with economic development theory that sees infrastructure as a pillar of development. This research identifies various challenges related to infrastructure sustainability. Thus, policy recommendations emphasize increased community participation, budget allocation for ongoing maintenance to maximize the long-term positive impact of infrastructure development.